3D-Printed Extracellular Matrix/Polyethylene Glycol Diacrylate Hydrogel Incorporating the Anti-inflammatory Phytomolecule Honokiol for Regeneration of Osteochondral Defects. Issue 11 (September 2020) - Zhu, Shouan; Chen, Pengfei; Chen, Yang; Li, Muzhi; Chen, Can; Lu, Hongbin
Background: Osteoarthritis is the leading cause of disability worldwide; cartilage degeneration and defects are the central features. Significant progress in tissue engineering holds promise to regenerate damaged cartilage tissue. However, a formidable challenge is to develop a 3-dimensional (3D) tissue construct that can regulate local immune environment to facilitate the intrinsic osteochondral regeneration. Purpose: To evaluate efficacy of a 3D-printed decellularized cartilage extracellular matrix (ECM) and polyethylene glycol diacrylate (PEGDA) integrated novel scaffold (PEGDA/ECM) together with the natural compound honokiol (Hon) for regenerating osteochondral defect. Study Design: Controlled laboratory study. Methods: We used a stereolithography-based 3D printer for PEGDA/ECM bioprinting. A total of 36 Sprague-Dawley rats with cylindrical osteochondral defect in the trochlear groove of the femur were randomly assigned into 3 different treatments: no scaffold implantation (Defect group), 3D printed PEGDA/ECM scaffold alone (PEGDA/ECM group), or Hon suspended in a 3D-printed PEGDA/ECM scaffold (PEGDA/ECM/Hon group). 12 rats that underwent only medial parapatellar incision surgery were used as normal controls. The femur specimens were postoperatively harvested at 4 and 8 weeks for gross, micro-CT, and histological evaluations. The efficacy of PEGDA/ECM/Hon scaffold on the release of proinflammatory cytokines from the macrophages stimulated by lipopolysaccharide (LPS) was evaluated in-vitro. Results: In vitro results determined that PEGDA/ECM/Hon scaffold could suppress the release of proinflammatory cytokines from macrophages that were stimulated by LPS. Macroscopic images showed that the PEGDA/ECM/Hon group had significantly higher ICRS scoring than that of defect and PEGDA/ECM groups. Micro-CT evaluation demonstrated that much more bony tissue was formed in the defect sites implanted with the PEGDA/ECM scaffold or PEGDA/ECM/Hon scaffold compared with the untreated defects. Histological analysis showed that the PEGDA/ECM/Hon group had a significant enhancement in osteochondral regeneration at 4 and 8 weeks after surgery in comparison with the ECM/PEGDA or defect group. Conclusion: This study demonstrated that 3D printing of PEGDA/ECM hydrogel incorporating the anti-inflammatory phytomolecule honokiol could provide a promising scaffold for osteochondral defect repair.